Strengthening the Framework for Post Program Monitoring. (Policy Papers; Policy Paper ;, 2016)
Post-Program Monitoring (PPM) is an important part of the Fund's safeguards architecture. It provides a framework for closer engagement with members that have substantial outstanding Fund credit but are no longer in a program relationship, and helps identify risks and provide advice on policies that will assist these members in repaying the Fund. The significant expansion in Fund credit since the global financial crisis, much of it through medium-term financing of members with high access levels, puts a premium on this form of monitoring. The design and implementation of the current policy can be strengthened.